Speech And Thought Representation of the Split Personality Between the Narrator and Tyler Durden In Fight Club By Chuck Palahniuk - Ariq Zufar Muhammad; Catur Kepirianto (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2021)
This research is to analyze the stylistics elements of speech and thought of the narrator’s and his split personality, Tyler Durden in Fight Club (1996) is Chuck Palahniuk. The analysis employs Geoffrey Leech and Michael Short’s theory of speech and thought representation as presented in Paul Simpson’s stylistics guidebook. The method of data collection is close reading the novel and then analyzing them with descriptive qualitative method. The research shows that the narrator is prominently represented thought representation while Tyler Durden most represented by speech representation. Through the progression of the plot’s beginning, middle, and end part, the narrator and Tyler’s characterizations and development as split personalities can be seen by their speech and thought representations. By analyzing both the narrator and Tyler Durden’s speech and thought representation, it can be concluded that linguistic style choices are essential tools used by the author to enhance the reading experience.Keywords: Fight Club; novel; stylistics; speech and thought representation; split personality